Developing a Circular Economy-Oriented Business Process Model for Sustainable Weaving Industries - Anresnani, Deririnda Setyo (Universitas Trunojoyo Madura, 2025)
This research aims to develop a circular economy-based business process model for the traditional weaving industry in Nusa Tenggara Timur (NTT), Indonesia. The study addresses the problem of waste generation and resource inefficiency in the existing linear production process, which relies heavily on synthetic dyes and lacks systematic reuse or recycling practices. By applying the Business Process Model and Notation (BPMN) and the Circular Business Model Canvas (CBMC), a redesigned process integrates waste recovery, reuse, and upcycling. Simulation results indicate that introducing natural dyeing, product diversification from leftover materials, and reverse logistics significantly reduce environmental impact while increasing revenue by 15–20%. This model demonstrates the feasibility of adopting circular principles in small-scale traditional industries, providing environmental benefits and economic resilience. The findings contribute to sustainable business practices and offer a replicable framework for similar sectors.